Moreninių nuogulų formavimasis dabartiniuose Grenlandijos ledynuose - Baltrūnas, Valentinas; Šinkūnas, Petras (2007)
The flight by plane along the western margin of the Greenland ice sheet for several hundred kilometres revealed the variety of forms and origin of landscape. The area of detai-led study was in Soudiwest Greenland, 20-30 km northeast of Kangerlussuaą in the margin of Russell glacier. Rather well exposed sections of basai ice were found at the northern margin of the Russell glacier. Lithological till samples were taken from the basai part of the ice, from the ablation till at die top of the glacier and from the end and lateral moraines. Preliminary results show that the amount of till material in basai part of the glacial ice comprises about 50% in average and the orientation of pebble long axes dip is to the SSW mainry. The results of grain size anarysis showed that the main part of clastic material in die ice of the basai part of the glacier is of silt and sand size (about 84%), much more then in the end, lateral and ablation moraines. The other part of the clastic material is composed of gravel and pebbles. The amount of this material is similar in the end moraines and comprises 43.63-60.94%.